DEVELOPMENT OF ANDROID-BASED EDUCATIONAL GAMES, LIGHT MATERIALS, AND OPTICAL TOOLS FOR CLASS VIII SMP/MTS - Desi Wulandari; Dinar Maftukh Fajar (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2022)
The purpose of this study is to describe the validity and students' responses to android-based educational games with Light and Optical Instruments for class VIII SMP/MTs. The method used in this study is the Research and Development (R&D) method with an analysis, design, development, implementation and evaluation (ADDIE) model. The trial subjects in this study consisted of 2 assessors of media experts, 2 assessors of material experts, 2 science teachers and class VIII B students of SMP Negeri 3 Bondowoso totaling 32 students. The instruments used are instruments or assessment sheets for media, material, science teachers and student response sheets. The results obtained that the validity of the game based on the assessment of media experts got a feasibility percentage of 86.67% (very valid), the material expert assessment got a feasibility percentage of 91.29%, (very valid) and user assessments (science teachers) got a feasibility percentage of 91, 79% (very valid). Judging from the students' responses with a small scale (6 students) that is getting a feasibility percentage of 82.13% (very valid) and students' responses with a small scale (32 students) getting a feasibility percentage of 81.1% (very valid). Therefore, it can be concluded that the development of android-based educational games for the material of Light and Optical Instruments for class VIII SMP/MTs is very valid for use in learning.